Mapping child and adolescent self‐reported symptom data to clinician‐reported adverse event grading to improve pediatric oncology care and research. Issue 1 (25th September 2019) - McFatrich, Molly; Brondon, Jennifer; Lucas, Nicole R.; Hinds, Pamela S.; Maurer, Scott H.; Mack, Jennifer W.; Freyer, David R.; Jacobs, Shana S.; Baker, Justin N.; Mowbray, Catriona; Wang, Mian; Castellino, Sharon M.; et al.
Abstract : Background: Clinicians are the standard source for adverse event (AE) reporting in oncology trials, despite the subjective nature of symptomatic AEs. The authors designed a pediatric patient‐reported outcome (PRO) instrument for symptomatic AEs to support the National Cancer Institute's Common Terminology Criteria for Adverse Events (CTCAE) (the Pediatric PRO‐CTCAE). The current study developed a standardized algorithm that maps all possible Pediatric PRO‐CTCAE response patterns to recommended CTCAE grades to improve the accuracy of AE reporting in pediatric oncology trials. Methods: Two rounds of surveys were administered to experienced cancer clinicians across 9 pediatric hospitals. In round 1, pediatric oncologists assigned CTCAE grades to all 101 possible Pediatric PRO‐CTCAE response patterns. The authors evaluated clinician agreement of CTCAE grades across response patterns and categorized each response pattern as having high or low agreement. In round 2, a survey was sent to a larger clinician group to examine clinician agreement among a select set of Pediatric PRO‐CTCAE response patterns, and the authors examined how clinical context influenced grade assignment. Results: A total of 10 pediatric oncologists participated in round 1. Of the 101 possible patterns, 89 (88%) had high agreement. The Light weighted kappa was averaged across the 10 oncologists (Light kappa = 0.73; 95% CI, 0.66‐0.81). A total of 139 clinicians participated in round 2. High clinician agreement remained for the majority of generic response patterns and the clinical context did not typically change grades but rather improved agreement. Conclusions: The current study provides a framework for integrating child self‐reported symptom data directly into mandated AE reporting in oncology trials. Translating Pediatric PRO‐CTCAE responses into clinically meaningful metrics will guide future cancer care and toxicity grading. Abstract : The authors have developed an algorithm that translates pediatric self‐reported symptomatic adverse event (AE) data into recommended Common Terminology Criteria for Adverse Events (CTCAE) grades to inform the clinicians' AE grading. As such, there currently is a framework for integrating self‐reported symptom data into mandated AE reporting in oncology trials, which could promote grading consistency, inform decision making, and improve patient safety.